1995
DOI: 10.1180/minmag.1995.59.394.06
|View full text |Cite
|
Sign up to set email alerts
|

Exsolution and alteration microtextures in alkali feldspar phenocrysts from the Shap granite

Abstract: Alkali feldspar phenocrysts (bulk composition Or75.oAb24.6Ano.4) in the subsolvus Shap granite comprise a fine-scale mixture of subregular pristine crypto-and micro-perthites with altered, micropore-rich feldspar with irregular microstructures. The regular perthites are strain-controlled intergrowths of Albite and/or Periclinetwinned albite exsolution lamellae within tweed orthoclase. The microperthites formed at ~< 590~ by heterogeneous nucleation of thin albite films which coarsened to > 1 ~tm length. Crypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Several studies showed that abundance of exsolution textures in alkali feldspar indicates extensive structural rearrangement of magmatic alkali feldspar at low (=400 °C) temperature (e.g. Parsons 1978;Brown and Parsons 1989;Worden et al 1990;Lee et al 1995;Walker et al 1995). The turbidity in alkali feldspars points to recrystallization driven by infiltration of aqueous fluid.…”
Section: T M Qadhimentioning
confidence: 99%
“…Several studies showed that abundance of exsolution textures in alkali feldspar indicates extensive structural rearrangement of magmatic alkali feldspar at low (=400 °C) temperature (e.g. Parsons 1978;Brown and Parsons 1989;Worden et al 1990;Lee et al 1995;Walker et al 1995). The turbidity in alkali feldspars points to recrystallization driven by infiltration of aqueous fluid.…”
Section: T M Qadhimentioning
confidence: 99%
“…The front of the turbid (patchperthite) zone intrudes and cuts the pristine zone, which contains semi -coherent microperthite lamellae. The Ab -rich lamellae in microperthite are more thread -like than the Ab -rich patches in patchperthite, and the interface between the albite lamellae and the alkali feldspar primary phase in microperthite is sharp (semi -coherent), whereas the interface in patchperthite is irregular (incoherent; Lee et al, 1995). The Ab -rich patches of patchperthite occur in either a vein form or a bead form.…”
Section: Textures Of Exsolution and Deuteric Sub-solidus Reactionsmentioning
confidence: 95%
“…1B); Ms -Bt granite, muscovite -biotite granite; Hb -Bt granite, hornblende -biotite granite; Bt granite, biotite granite (Yuguchi et al, 2010). croscopy (SEM) have shown that alkali feldspar phenocrysts in the Shap granite of Cumbria, northwest England, have undergone both an exsolution reaction to form "coherent" cryptoperthite and a deuteric reaction to form "incoherent" patchperthite (Worden et al, 1990;Waldron and Parsons, 1992;Waldron et al, 1994;Lee et al, 1995;Walker et al, 1995;Lee and Parsons, 1997). Hashimoto et al (2005A) suggested that an exsolution reaction in alkali feldspar is responsible for the formation of "semi -coherent" microperthite with micrometer -scale Ab -rich lamellae and cryptoperthite with a nanometer -scale Ab -rich phase (zigzag or lozenge form).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, most of alkali feldspars in granites are reorganized to form patch microperthites with pervasive turbidity over a grain (e.g., Lee et al, 1995;Lee and Parsons, 1997;Hashimoto et al, 2005a;Yuguchi and Nishiyama, 2007), although relatively pristine part of cryptoperthite is still few remained Lee and Parsons, 1997). Thus, perthitic textures of alkali feldspars become a very important tool to clarify the cooling histo-ries of host plutons during magmatic to hydrothermal stages (Brown and Parsons, 1994;Parsons and Lee, 2009).…”
Section: Introductionmentioning
confidence: 99%